PERBEDAANWAKTU TRANSPORMUKOSILIARHIDUNG PEKERJASTASIUNPENGISIANBAHAN BAKAR UMUM (SPBU) DIBANDINGBUKAN PEKERJASPBU - , Didit Yudhanto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The nose is the first line of nasal passage defense against air pollutants. The nasal mucociliary transport is one of the nasal passage defense mechanism. Direct expose to gasoline, an irritant agent, can induce hyper-reactivity and inflammation of nasal mucous membrane. Those processes will interfere the nasal mucociliary transport time. Purpose: The purpose of this study is to know the difference medical evidence between nasal mucociliary transport time of gasoline station workers and none gasoline station workers. Method: This study used cross sectional design, with 34 subjects in each group, gasoline exposed group and none gasoline exposed group. The saccharine test was carried out to measure nasal mucociliary transport time in both of group. Statistical analysis tindependent test or Mann-Whitney U test was used to analyze the difference of nasal mucociliary transport time between each group, and linear regression was used for further analysis. Result: The mean of nasal mucociliary transport time in gasoline exposed group was 12,74 minute (SDÂ±5,57), range 6,10 â 28,65 minute and in none exposed group was 7,8 minute (SDÂ±2,03), range 3,50 â 11,35 minute. There was statistically significant difference of nasal mucociliary transport time between gasoline exposed group and none gasoline exposed group. Conclusion: There is statistically significant difference of nasal mucociliary transport time between gasoline station workers and none gasoline station workers.